2012
DOI: 10.1002/ange.201200689
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Dramatic Axial Ligand Effects: Closed‐Shell MnVO Complexes Use Exchange‐Enhanced Open‐Shell States to Mediate Efficient H Abstraction Reactions

Abstract: Spinzustandseffekte: Trotz geschlossenschaliger Singulett‐Grundzustände ist in [(Cz)MnVO]‐Komplexen der reaktive Zustand ein offenschaliges B‐Triplett (SB=1), das hohen Oxyl‐Radikalcharakter hat und einen durch austauschverstärkte Reaktivität (EER) stabilisierten Übergangszustand (TS) aufweist (siehe Bild). Der drastische axiale Ligandeneffekt hat seine Ursache in der EER dieses Zustands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…170 In a separate computational study, Shaik and coworkers proposed that the origin of the rate enhancement was due to a low-energy triplet transition state, as the most likely C–H bond cleavage pathway. 171 Higher-level NEVPT2:CAS calculations have shown that the energetically favored ground state is the singlet state for the same six-coordinate complexes, and showed that the singlet-triplet gap is much larger than predicted by the former DFT calculations. The six-coordinate complexes [Mn V (O)(X)(TBP 8 Cz)] − (X = CN − , F − ) also exhibited dramatically enhanced OAT rates relative to the non-axially ligated Mn V (O)(TBP 8 Cz) in reactions with sulfide substrates, including para -substituted thioanisole derivatives.…”
Section: Metal-oxo Porphyrinoid Complexes As Models For Biological Oxmentioning
confidence: 91%
“…170 In a separate computational study, Shaik and coworkers proposed that the origin of the rate enhancement was due to a low-energy triplet transition state, as the most likely C–H bond cleavage pathway. 171 Higher-level NEVPT2:CAS calculations have shown that the energetically favored ground state is the singlet state for the same six-coordinate complexes, and showed that the singlet-triplet gap is much larger than predicted by the former DFT calculations. The six-coordinate complexes [Mn V (O)(X)(TBP 8 Cz)] − (X = CN − , F − ) also exhibited dramatically enhanced OAT rates relative to the non-axially ligated Mn V (O)(TBP 8 Cz) in reactions with sulfide substrates, including para -substituted thioanisole derivatives.…”
Section: Metal-oxo Porphyrinoid Complexes As Models For Biological Oxmentioning
confidence: 91%
“…This stabilization energy is comparable to the calculated energy barrier difference between singlet and triplet pathways for this species. 311 The kinetic isotope effect (KIE) for hydrogen/deuterium HAT has been proposed to be a good mechanistic probe to probe the reactive spin state of a reaction. Theoretical calculations have shown that different spin states can display very different KIEs.…”
Section: C−h Functionalization Reactions Mediated By Oxoiron(iv) Porp...mentioning
confidence: 97%
“…This concept can be utilized to analyze the preference for the triplet state in oxoMn(V)-mediated C–H activation in Figure 32 . 311 The transition state on the S = 0 surface is an open shell singlet with no spin-exchange interactions, while for the triplet surface, three exchange interactions are present. The overall stabilization effect in the triplet state can be estimated by 3 K dd – Δ E orb ( d xy → d xz/yz ), in which Δ E orb ( d xy → d xz/yz ) is the energy needed for orbital excitation from d xy to d xz/yz .…”
Section: C–h Functionalization Reactions Mediated By Oxoiron(iv) Porpmentioning
confidence: 99%
See 2 more Smart Citations